E-Assessment, Inequity and Accountability in the New Normal Era and Beyond in Nigerian Universities - Abdul-Wahab Ibrahim; Abdullahi Iliyasu (Journal of Digital Learning and Education, 2021)
The study examined the perceived conduct of e-assessment of undergraduate courses in Nigerian universities and compared access to e-assessment among undergraduate students in universities in the country. It also determined the relationship between e-assessment-based accountability and test fairness in the conduct of e-assessment in Nigerian universities. These were with a view to improving the assessment outcome directed towards certifying the quality in education by the Nigerian universities. The study adopted a mixed research approach combining both descriptive survey and focus group designs. The population consisted of all undergraduate students who registered for their degree courses at the government and privately-owned universities during 2019/2020 academic session. The sample consisted of intact classes of 450 Parts 2, 3, and 4 undergraduate students who registered for their degree courses. A 32-item self-developed instrument was used in the study. The qualitative data was collected via focus group. Data were analysed using independent t-test, and Pearson Product Moment Correlation statistical methods. The results showed that there existed a significant difference in students’ perception of the conduct of e-assessment in Nigerian universities. Also, there was a significant difference in access to e-assessment among undergraduate students in the universities. Further, a significant relationship existed between e-assessment-based accountability and test fairness in the conduct of e-assessment in Nigerian universities. The study concluded that improper conduct of e-assessment forms a major threat to the fairness and validity of online assessment of students. It was recommended that universities’ Management should employ equitable strategies in the design, development and administration of the e-assessment on campuses in the country.